2021
DOI: 10.1039/d0ob02364g
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free generation of acyl radicals induced by visible light in water to construct C–N bonds

Abstract: A new route to produce acyl radicals by the cleavage of Csp2–Csp2 bonds of α-diketones irradiated by visible light was developed and hydroxylamides or amides were selectively synthesized in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In 2021, Yao and co-workers achieved the synthesis of amides 91 by utilizing a-diketones 90 as acyl radical 41A precursors, nitrosoarenes 22 as a surrogate of amines, and NaCl as an additive under purple LEDs (Scheme 41). 103 A variety of adiketones and nitrosoarenes were tolerated well under the reaction conditions, and furnished the respective amides in good yields.…”
Section: From A-diketonesmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2021, Yao and co-workers achieved the synthesis of amides 91 by utilizing a-diketones 90 as acyl radical 41A precursors, nitrosoarenes 22 as a surrogate of amines, and NaCl as an additive under purple LEDs (Scheme 41). 103 A variety of adiketones and nitrosoarenes were tolerated well under the reaction conditions, and furnished the respective amides in good yields.…”
Section: From A-diketonesmentioning
confidence: 97%
“…Under visible light irradiation, charge carriers of h + and e À are generated on the surface of the In 2016, Yao and co-workers described a visible lightpromoted Ag/g-C 3 N 4 nanocomposite (photocatalyst)-catalyzed amidation of aromatic aldehydes 1 under visible light illumination (Scheme 34(a)). 95 Moreover, the reaction could also take place under sunlight to afford the desired amides 80 in moderate yields. Expectedly, aromatic aldehydes bearing electron-withdrawing groups reacted more efficiently than those having electron-donating groups.…”
Section: Strategies Based On Heterogeneous Catalystsmentioning
confidence: 99%
“…as the only additive. 6 Furthermore, Cao et al 7 reported a catalyst-free Meerwein–Ponndorf–Verley–type reduction of carbonyl compounds in isopropanol and decarbonylation of diaryl ketones when irradiated by ultraviolet (UV) light. These results intrigued us, and we hypothesized that light should be enough to promote electron transfer between conjugated unsaturated compounds and electron donors such as salts, amines, or inorganic bases (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…S2 and S3, Figure S2). In addition, the acetyl radical was trapped by TEMPO, and a trace of the pinacol-coupling product ( 8 ) was detected, which all suggest a radical pathway . Acetic acid can increase the reaction rate, without which the conversion ratio and regioselectivity were low (Eqns.…”
mentioning
confidence: 99%